Bacterial Cellulose Properties Fulfilling Requirements for a Biomaterial of Choice in Reconstructive Surgery and Wound Healing - Jankau, Jerzy; Błażyńska‐Spychalska, Agata; Kubiak, Katarzyna; Jędrzejczak-Krzepkowska, Marzena; Pankiewicz, Teresa; Ludwicka, Karolina; Dettlaff, Aleksandra; Pęksa, Rafał (Frontiers in Bioengineering and Biotechnology, 2022)
Although new therapeutic approaches for surgery and wound healing have recently made a great progress, there is still need for application of better and use novel methods to enhance biocompatibility as well as recovery and healing process. Bacterial Cellulose (BC) is natural cellulose in the form of nanostructure which has the advantages of being used in human body. The medical application of BC in reconstructive, cardiac and vascular surgery as well as wound healing is still under development, but without proved success of repetitive results. A review of studies on Bacterial Cellulose (BC) since 2016 was performed, taking into account the latest reports on the clinical use of BC. In addition, data on the physicochemical properties of BC were used. In all the works, satisfactory results of using Bacterial Cellulose were obtained. In all presented studies various BC implants demonstrated their best performance. Additionally, the works show that BC has the capacity to reach physiological as well as mechanical properties of relevance for various tissue replacement and can be produced in surgeons as well as patient specific expectations such as ear frames, vascular tubes or heart valves as well as wound healing dressings. Results of those experiments conform to those of previous reports utilizing ADM (acellular dermal matrix) and demonstrate that the use of BC has no adverse effects such as ulceration or extrusion and possesses expected properties. Based on preliminary animal as well as the few clinical data BC fittings are promising implants for various reconstructive applications since they are biocompatible with properties allowing blood flow, attach easily to wound bed and remain in place until donor site is healed properly. Additionally, this review shows that BC can be fabricated into patient specific shapes and size, with capability to reach mechanical properties of relevance for heart valve, ear, and muscle replacement. Bacterial cellulose appears, as shown in the above review, to be one of the materials that allow extensive application in the reconstruction after soft tissue defects. Review was created to show the needs of surgeons and the possibilities of using BC through the eyes and knowledge of biotechnologists.